2017
DOI: 10.3892/ijmm.2017.3047
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin ameliorates ionizing radiation-induced apoptosis in the thymus by activating the AKT/sirtuin 1 pathway in mice

Abstract: Simvastatin is a HMG-CoA reductase inhibitor widely used to lower plasma cholesterol and to protect against cardiovascular risk factors. The aim of this study was to investigate whether simvastatin attenuates ionizing radiation-induced damage in the mouse thymus and to elucidate the possible mechanisms invovled. For this purpose, male C57BL/6J mice aged 6 weeks were used and exposed to 4 Gy 60Co γ-radiation with or without simvastatin (20 mg/kg/day, for 14 days). Apoptosis was determined by terminal deoxynucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…We further used simvastatin, atorvastatin, and rosuvastatin to block lipid metabolism, only simvastatin protected male mice against radiation‐induced toxicity. Of note, simvastatin had been reported to mitigate radiation‐induced organ injuries, covering small intestine and hematopoiesis system . However, the mice in these studies were exposed to total body irradiation only which caused acute hematopoietic syndrome not GI syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further used simvastatin, atorvastatin, and rosuvastatin to block lipid metabolism, only simvastatin protected male mice against radiation‐induced toxicity. Of note, simvastatin had been reported to mitigate radiation‐induced organ injuries, covering small intestine and hematopoiesis system . However, the mice in these studies were exposed to total body irradiation only which caused acute hematopoietic syndrome not GI syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whether therapeutic approaches for radiation‐caused toxicity representing sexual dimorphism remains poorly understood, which possesses pivotal clinical value. As a HMG‐CoA reductase inhibitor and an anticholesterol drug, simvastatin has also been reported to mitigate radiation toxicity . However, the evolution of males and females facilitates comprehension of sex‐specific physiology and, consequently, differential susceptibility to diseases with particular reference to those involving energy metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, C57BL/6J mice were pretreated with simvastatin (20 mg/kg) on three different days in a seven-day cycle. Simvastatin intensified the expression of Bcl-2 and PARP and reduced p53/p-p53 [ 88 ]. In 2013, Kok et al investigated the effects of simvastatin in collagen-induced arthritis (CAI) and reported that simvastatin downregulated TNF-α expression and CCL20 production.…”
Section: Evidence For Statins In the Regulation Of Sirtuin-mediated A...mentioning
confidence: 99%
“…In animal and cell culture models, statins ameliorated radiation-induced inflammation and fibrosis in different tissues [ 153 , 154 , 155 ]. When their effect on the heart and blood vessels was specifically assessed, atorvastatin ameliorated radiation-induced cardiac fibrosis, prevented vascular damage, reduced endothelial cell apoptosis, and promoted the healing of the radioactive injuries [ 124 , 156 , 157 ].…”
Section: Radiotherapymentioning
confidence: 99%